Comprehensive Physiology 2021
DOI: 10.1002/cphy.c210008
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Rhythm of Thermoregulation Modulates both the Sleep/Wake Cycle and 24 h Pattern of Arterial Blood Pressure

Abstract: Borbély proposed an interacting two-component model of sleep regulation comprising a homeostatic Process S and a circadian Process C. The model has provided understanding of the association between core body temperature (CBT) as a key element of Process C that is deterministic of sleep onset and offset. However, it additionally provides a new perspective of the importance of the thermoregulatory mechanisms of Process C in modulating the circadian rhythm of arterial blood pressure (ABP). Herein, we examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 130 publications
0
12
0
Order By: Relevance
“…Meanwhile, the circadian pattern of core body temperature, resulting from the endogenous circadian rhythm of heat production and loss, 32 affects the 24-hour pattern of BP through vasomotor modulation of the AVAs. 12 The clinical implication of our findings is that ST manipulation can contribute to BP regulation, such as by lowering BP variability and nighttime BP. Our results suggested that smaller changes in ST, especially in DST during the daytime, may lead to lower ambulatory BP variability.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Meanwhile, the circadian pattern of core body temperature, resulting from the endogenous circadian rhythm of heat production and loss, 32 affects the 24-hour pattern of BP through vasomotor modulation of the AVAs. 12 The clinical implication of our findings is that ST manipulation can contribute to BP regulation, such as by lowering BP variability and nighttime BP. Our results suggested that smaller changes in ST, especially in DST during the daytime, may lead to lower ambulatory BP variability.…”
Section: Discussionmentioning
confidence: 70%
“…Meanwhile, the circadian pattern of core body temperature, resulting from the endogenous circadian rhythm of heat production and loss, 32 affects the 24-hour pattern of BP through vasomotor modulation of the AVAs. 12…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, the venous return and the cardiac output are also modulated by the heat transfer from skin to blood, and subsequently to the body core ( 56 ). However, it is worth to highlight that the superficial microcirculation is influenced also by local factors, hence, it could be licit to suppose that the not optimal correspondence between the estimated and measured HRV metrics is related to different physiological mechanisms underlying the cardiac rhythm and the skin temperature modulations ( 57 ). In addition, it is useful to highlight that PPG signals could vary based on the measurement site and the skin temperature.…”
Section: Discussionmentioning
confidence: 99%